A genomic copy number signature predicts radiation exposure in post‐Chernobyl breast cancer. Issue 6 (10th May 2018) - Wilke, Christina M.; Braselmann, Herbert; Hess, Julia; Klymenko, Sergiy V.; Chumak, Vadim V.; Zakhartseva, Liubov M.; Bakhanova, Elena V.; Walch, Axel K.; Selmansberger, Martin; Samaga, Daniel; Weber, Peter; Schneider, Ludmila; et al.
Abstract : Breast cancer is the second leading cause of cancer death among women worldwide and besides life style, age and genetic risk factors, exposure to ionizing radiation is known to increase the risk for breast cancer. Further, DNA copy number alterations (CNAs), which can result from radiation‐induced double‐strand breaks, are frequently occurring in breast cancer cells. We set out to identify a signature of CNAs discriminating breast cancers from radiation‐exposed and non‐exposed female patients. We analyzed resected breast cancer tissues from 68 exposed female Chernobyl clean‐up workers and evacuees and 68 matched non‐exposed control patients for CNAs by array comparative genomic hybridization analysis (aCGH). Using a stepwise forward–backward selection approach a non‐complex CNA signature, that is, less than ten features, was identified in the training data set, which could be subsequently validated in the validation data set ( p value < 0.05). The signature consisted of nine copy number regions located on chromosomal bands 7q11.22‐11.23, 7q21.3, 16q24.3, 17q21.31, 20p11.23‐11.21, 1p21.1, 2q35, 2q35, 6p22.2. The signature was independent of any clinical characteristics of the patients. In all, we identified a CNA signature that has the potential to allow identification of radiation‐associated breast cancer at the individual level. Abstract : What's new? Exposure to ionizing radiation during medical procedures or following nuclear accidents can increase breast cancer risk by inducing DNA double‐strand breaks that potentially lead to DNA copy number alterations. In this study, the authors identified a genomic copy number signature associated with radiation exposure in breast cancers in women who were exposed to ionizing radiation as Chernobyl clean‐up workers or accident evacuees. The signature, composed of nine genomic copy number regions, enabled the calculation of a breast cancer radiation‐exposure risk score, which was independent of clinical characteristics. The findings cast light on a new approach to radiation‐induced breast cancer detection.